(untitled) (Papeles, 2025)
This article aims to explore the origins of home visits in Argentina. The relevance of this inquiry lies in the fact that home visits continue to be a tool of intervention that remains part of the professional practice of social workers. Therefore, this historical review allows for the identification of certain lines of continuity with the present. To this end, the focus is placed on the Society of the Ladies of Saint Vincent de Paul, a charitable organization that, since the mid-19th century, has carried out its work in the city of Buenos Aires, grounded in the religious principles promoted by Saint Vincent de Paul. It is important to note that this organization was composed exclusively of women. Thus, the article seeks to analyze the role of these Vincentian ladies in relation to the gender stereotypes that characterized the studied period. Moreover, it specifically examines the home visits carried out by the organization and reflects on how these visits represented, for the Vincentian women, an unrecognized form of labor and an entry into the public sphere.